Change - Eswaran, Vijay, Dato'; VStudios ([S.l.] : VStudios, 2008)
Dato' Vijay Eswaran shares the importance of change in people live, most importantly in multilevel networking. Change is the onlu thing that will save people. People who change is people who succeed
Title from container
DVD format
Keywords: Multilevel marketing; Direct marketing